Designing a self-reliance model for households with food insecurity in Iran - Mohammad Reza Honarvar; Masoomeh Gholami (Discover Food)
Abstract Food insecurity refers to the inadequate access to sufficient, nutritious food necessary for proper growth, development, and overall well-being. This study aimed to develop a self-reliance model for food-insecure households through a mixed-methods approach. The research examined the feasibility of an empowerment and self-reliance framework at the district and provincial levels, ensuring its adaptation to local infrastructure and regional characteristics. A comprehensive review of published studies and practical experiences addressing food insecurity in Iran and globally was conducted. Additionally, interviews were held with key experts in the field to explore challenges, barriers to implementation, effective intervention strategies, and optimal execution methods. The findings were then analyzed thematically, resulting in the formulation of a proposed model. We outline a structured seven-step process to promote household self-reliance and empowerment in the context of food insecurity. The key steps include: (1)policy-making and legislation, (2)infrastructure preparation, (3)identification of affected households and available resources, (4)assessment of current conditions for implementation, (5)execution of targeted interventions and educational programs, (6)monitoring, assessment, and sustainability planning, and (7)evaluation and program refinement. Addressing poverty and food insecurity necessitates a coordinated, systematic, and enduring approach to self-reliance and empowerment initiatives, backed by robust legislative support. These programs must be tailored to local capacities, regional conditions, and actively involve community members in decision-making, implementation, monitoring, and refinement to ensure long-term success.